ANALISIS PERKUATAN BANGUNAN BAWAH JEMBATAN DENGAN RIP-RAP - N. Retno Setiati; Elis Kurniawati (Direktorat Bina Teknik Jalan dan Jembatan, 2021)
In general, existing bridges in Indonesia that were built in the 1980s do not take into account the morphological shape of the river flow. This has an impact on the bridge that was built at the river's location to collapse due to damaged pillars. Damage to the pillar was caused by scouring of the river flow that occurred during a certain period and the collapse did not occur suddenly. This research was conducted to determine the potential occurrence of river flow scouring on the existing bridge pillars that occurs within a certain time period. Scour depth analysis was carried out using several empirical methods and using the Hydrologic Engineering Center's River Analysis System (HEC-RAS) program. Case studies were carried out on the Cipamingkis Bridge (after retrofitting) and the Cipunegara Bridge. In the case study, the depth of the scour that occurred in each bridge pillar will be compared for the 100 year return period of flooding. Based on the results of the analysis, the scour depth of the Cipamingkis bridge pillars (after strengthening) for the 100 year return period of flooding is 5 m. While the scour depth for the Cipunegara Bridge for the 100 year return period of flooding is 7 meters. The scour depth of the Cipunegara bridge pillar is greater than that of the Cipamingkis bridge. Mitigation technology to avoid the collapse of the pillars of the Cipunegara and Cipamingkis bridges is to construct a river flow protection structure and construct a pillar protection structure. Making rip-rap around bridge pillars is one type of prevention that is done so that the bridge pillars don't suddenly collapse. Reinforcement of rip-rap on the pillars of the Cipunegara and Cipamingkis bridges can reduce the occurrence of scouring processes by 60% for the 100 year return period of flooding. Keywords: bridge, pier, existing, scourings, Hec-ras, rip-rap